2004
DOI: 10.1038/sj.jhh.1001785
|View full text |Cite
|
Sign up to set email alerts
|

Independent association between inflammatory markers (C-reactive protein, interleukin-6, and TNF-α) and essential hypertension

Abstract: High blood pressure (HBP) has been associated with elevated C-reactive protein (CRP), a marker of chronic mild inflammation. However, the association between HBP and other inflammatory markers, particularly interleukin 6 (IL-6) and tumour necrosis alpha (TNF-a), has not been evaluated in well-controlled studies. We examined the cross-sectional relationship between IL-6, TNF-a, and CRP and HBP in a random sample of 196 healthy subjects. All markers were measured in duplicate with high-sensitivity ELISA tests. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
341
3
23

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 527 publications
(388 citation statements)
references
References 39 publications
21
341
3
23
Order By: Relevance
“…In a cross-sectional survey of 8347 apparently healthy Korean individuals, Sung et al 1 found that the prevalence of hypertension was 1.267-, 1.253-and 1.451 times higher in subjects from the second, third and fourth quartiles of the C-reactive protein (CRP) distribution, respectively, compared with subjects in the first quartile, even after the adjustment for many confounders (CRP level ranges for the first and fourth quartiles were 0.1-0.3 and 1.2-11 mg l − 1 , respectively). Similarly, Bautista et al 2 showed that patients in the third and fourth quartiles of the interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) distribution were more likely to have hypertension compared with patients in the first quartile. These and other studies 3 recruited apparently healthy individuals and assessed inflammatory markers along with a number of laboratory, clinical and demographic features described as independent predictors of elevated blood pressure.…”
Section: Human Studies Identifying the Role Of Inflammation In Hypertmentioning
confidence: 97%
“…In a cross-sectional survey of 8347 apparently healthy Korean individuals, Sung et al 1 found that the prevalence of hypertension was 1.267-, 1.253-and 1.451 times higher in subjects from the second, third and fourth quartiles of the C-reactive protein (CRP) distribution, respectively, compared with subjects in the first quartile, even after the adjustment for many confounders (CRP level ranges for the first and fourth quartiles were 0.1-0.3 and 1.2-11 mg l − 1 , respectively). Similarly, Bautista et al 2 showed that patients in the third and fourth quartiles of the interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) distribution were more likely to have hypertension compared with patients in the first quartile. These and other studies 3 recruited apparently healthy individuals and assessed inflammatory markers along with a number of laboratory, clinical and demographic features described as independent predictors of elevated blood pressure.…”
Section: Human Studies Identifying the Role Of Inflammation In Hypertmentioning
confidence: 97%
“…Pathophysiologic studies have shown that both are related to inflammation. 1,2 Investigations in this field and development of new effective treatment strategies are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Many inflammatory markers, such as Creactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and white blood cell count were proved in association with hypertension and its complications. 1,2 More recently, increasing data show that inflammation may be related to AF. 3,4 Bruins et al 3 has reported that frequency of AF was increased after cardiac surgery, and changes in levels of CRP, complement-CRP complexes after surgery, and cardiopulmonary bypass (CPB) were responsible for the occurrence of postoperative AF.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Raised concentrations of inflammatory markers have been associated with increased incidences of cardiovascular diseases. [10][11][12][13][14][15][16][17] Furthermore, men who have been exposed to elevated levels of inflammatory proteins many years earlier have higher fatality in future coronary events, with a higher proportion of CHD deaths and less non-fatal myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%